Eimeria tenella Infection Induces Local Gamma Interferon Production and Intestinal Lymphocyte Subpopulation Changes - Yun, Cheol H. (American Society for Microbiology, 2000)
The role of intestinal lymphocytes and gamma interferon (IFN-γ) production in protective immunity to Eimeria tenella infection was evaluated in two inbred strains of chickens (SC and TK) that display different patterns of susceptibility to coccidiosis. Oral inoculation of either strain with E. tenella led to parasite invasion of the intestinal cecum and cecal tonsils. Greater fecal oocyst shedding was seen in TK chickens. Flow cytometric analyses of cecal tonsil lymphocytes demonstrated greater numbers of CD4(+) and T-cell receptor γδ-positive (TCR1(+)) cells in SC chickens and elevated numbers of CD8(+) and TCR2(+) cells in TK chickens following primary infection. IFN-γ mRNA expression was significantly increased in cecal tonsil and intraepithelial lymphocytes at days 6 and 8, respectively, after primary infection in SC compared to TK chickens. While no differences were noted between cecal tonsil lymphocytes of the two strains following secondary infection, TK chickens showed elevated IFN-γ transcript levels in intestinal intraepithelial lymphocytes at this time. Selective depletion of CD4(+), but not CD8(+), cecal tonsil lymphocytes in SC chickens resulted in a reduced IFN-γ mRNA expression, indicating that CD4(+) cells are the primary source of this cytokine. Collectively, these results indicate that local lymphocyte responses and production of IFN-γ are influenced by host genetic factors.